1994
DOI: 10.1007/bf01553487
|View full text |Cite
|
Sign up to set email alerts
|

Possible origin of a B chromosome deduced from its DNA composition using double FISH technique

Abstract: Double fluorescent in situ hybridization (FISH) with two DNA probes (a 180 bp tandemly repeated DNA and ribosomal DNA) was performed in embryo cells of the grasshopper Eyprepocnemis plorans. Repetitive DNA was present in most standard chromosomes (excepting 7, 8 and 10) and in the proximal two-thirds of the B chromosome, which was its major location in the complement. Ribosomal DNA was present distally on the B, and in the active nucleolar organizer regions (NORs) of the X, 9, 10 and 11 chromosomes. A small nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 21 publications
4
82
0
Order By: Relevance
“…In contrast, it is now known that the human a-satellite DNA contains a 17 bp CENP-B box that binds the protein CENP-B (Masumoto et a!., 1989) and is directly involved in centromere function (Haaf et a!., 1992). Another possibility is that the 180 bp repeat has something to do with the regulation of the expression of the ribosomal genes to which it is always adjacent. Double fluorescence in situ hybridization (FISH) with this tandem repeat and rDNA showed that i) the repetitive DNA is present in paracentromeric regions of all A chromosomes except 7, 8 and 10, ii) the rDNA is located also paracentromerically on all A chromosomes, although the most prominent hybridization signals are those of the rRNA gene clusters that are usually active on the 9, 10, 11 and X chromosomes, and iii) the B2 chromosome is mainly composed of these two DNA sequences (Lopez- Leon et al, 1994). In all A chromosomes, except the X chromosome, the rDNA is located between the centromere and the repetitive DNA.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, it is now known that the human a-satellite DNA contains a 17 bp CENP-B box that binds the protein CENP-B (Masumoto et a!., 1989) and is directly involved in centromere function (Haaf et a!., 1992). Another possibility is that the 180 bp repeat has something to do with the regulation of the expression of the ribosomal genes to which it is always adjacent. Double fluorescence in situ hybridization (FISH) with this tandem repeat and rDNA showed that i) the repetitive DNA is present in paracentromeric regions of all A chromosomes except 7, 8 and 10, ii) the rDNA is located also paracentromerically on all A chromosomes, although the most prominent hybridization signals are those of the rRNA gene clusters that are usually active on the 9, 10, 11 and X chromosomes, and iii) the B2 chromosome is mainly composed of these two DNA sequences (Lopez- Leon et al, 1994). In all A chromosomes, except the X chromosome, the rDNA is located between the centromere and the repetitive DNA.…”
Section: Discussionmentioning
confidence: 96%
“…In most cases, this situation occurs due to the origin of B chromosomes, which can have the sex chromosome as an ancestor. An example of this derivation is the B 2 chromosome of Eyprepocnemis plorans (López-León et al, 1994), where repetitive DNA and rDNA sequences are located respectively at the proximal and distal regions as in X chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Slides were stored at 601C overnight before in situ hybridization. FISH was performed with two different DNA probes: pTa71, which contains a 9-kb EcoRI repeat unit of rDNA isolated from Triticum aestivum (Gerlach and Bedbrook, 1979), and pEpD15, which contains a 180 pb DraI fragment of a tandemly repetitive DNA isolated from E. plorans (Ló pez- Leó n et al, 1994Leó n et al, , 1995b. The probe DNA was labelled by nick translation with Fluorogreen 11-dUTP or Fluorored 11-dUTP, using standard techniques.…”
Section: Methodsmentioning
confidence: 99%
“…These B chromosomes are mainly made up of two repetitive DNAs, that is rDNA and a 180 bp satDNA, which are also present in many A chromosomes (Ló pez-Leó n et al, 1994, 1995bCabrero et al, 1999). To ascertain the origin of these B chromosomes is, therefore, necessary to investigate the presence and chromosome distribution of these two repetitive DNAs in geographically distant E. plorans populations as well as in some other closely related species, since such a study might uncover the ancestral patterns and the evolutionary pathways that could explain the present chromosome distribution.…”
Section: Introductionmentioning
confidence: 99%